Pendampingan Menulis Artikel bagi Guru PAI Pada Kota Pangkalpinang dan Kabupaten Bangka - Munawaroh, Ella; Irawan, Dody; Adib, Noblana; Fajrin, Rulli; Sanawiyah, Nelly (AL QUWWAH : Jurnal Pengabdian Masyarakat, 2023)
Apart from educating and teaching, teachers have an obligation to write scientific papers. Assistance in writing articles for teachers is needed to change their mindset that writing is difficult. This activity focuses on basic concepts, techniques and strategies in writing articles as well as providing directions and information for teachers about journals as a publication medium. The method of accompaniment and participant participation is used with a classical-individual approach to achieve the objectives of the activity. Based on the stages carried out in this mentoring activity, several scientific articles were developed based on research results written by twelve teachers and six assistants who were formed in the writing activity group. In addition, in this mentoring, there are six scientific articles that are appropriate and have been published in edugama journals (educational and socio-religious journals) accredited by Sinta 5. Through this scientific article writing assistance activity as well, teachers gain knowledge, motivation and experience in writing articles, which they can then develop again after the completion of this mentoring activity. Selain mendidik dan mengajar, guru memiliki kewajiban untuk menulis karya ilmiah. Pendampingan penulisan artikel bagi guru sangat diperlukan untuk mengubah mindset mereka bahwa menulis itu sulit. Kegiatan ini berfokus pada konsep dasar, teknik dan strategi dalam penulisan artikel serta memberikan arahan dan informasi bagi guru tentang jurnal sebagai media publikasi. Digunakan metode tindakan pendampingan dan partisipasi peserta dengan pendekatan klasikal-individual untuk mencapai tujuan kegiatan. Berdasarkan tahapan yang dilaksanakan kegiatan pendampingan ini menghasilkan beberapa artikel ilmiah yang dikembangkan dari hasil penelitian yang ditulis oleh dua belas guru dan enam pendamping yang tebentuk dalam kelompok kegiatan penulisan. Selain itu, dalam pendampingan ini, ada enam artikel ilmiah yang layak dan telah dipublikasikan pada jurnal edugama (jurnal kependidikan dan sosial keagamaan) terakreditasi sinta 5. Melalui kegiatan pendampingan penulisan artikel ilmiah ini juga, para guru mendapatkan pengetahuan, motivasi dan pengalaman dalam penulisan artikel ilmiah yang selanjutnya dapat mereka kembangkan kembali setelah selesainya kegiatan pendampingan ini